Influencia del clima laboral en el desempeño de los colaboradores del Banco Caja Social de la oficina Venecia av. 68 en la jornada básica y adicional (2021)
This research focused on determining the influence of the working climate on the performance of the collaborators of Banco Caja Social of the Av. 68 Venecia office on the basic and additional day, to accomplish the objectives a quantitative research of a descriptive cross-cutting type was carried out, as an information gathering technique the duly structured survey was applied taking into account the dimensions of the working climate and the characteristics of the work